Influence of literacy on two generations, literate and non-literate generation, of Arratia valley - Iglesias Chaves, Aitor; Abasolo Isasa, Juan; Etxebarria Lejarreta, Aintzane; Ensunza Aldamizetxebarria, Ariane (Huarte de San Juan. Filología y Didáctica de la Lengua, 2020)
The objective of this work is to check the influence of literacy on the vernacular of the Basque-speaking area of the Arratia valley. To this end, we have analyzed the linguistic distance between two generations of this valley with respect to standard Basque: a non-Basque-literate generation (45-50); and the other, which is literate in Basque (20-25 years). The methodology for analyzing the data is divided into three steps: the standardization of the data, the calculation of the linguistic distance; and, finally, a multiple correspondence analysis (MCA). With the standardized data we have performed two analyzes: on the one hand the RIV linguistic distance has been calculated using the Diatech program and, sencondly, a multivariate analysis has been performed for categorical data using FactoMineR pogrammed in the R language. The results show us that there is, in fact, a slight movement in the vernacular of the literate generations towards the use of forms typical of the standard that are unknown in non-basque-literate generation’s vernacular.
Keywords: Education; literacy; standard